Education on Increasing Sales of Agricultural Products with Social Media at the Sabilulungan Women Farmers Demplot Group in Sumedang - Deden Rudiansyah (Research Collaboration Community (RCC), 2021)
Community Service is one of the Tri Dharma of Higher Education, especially at Garut University, it is hoped that with this community service the existence of universities can contribute to the development of scientific application to the community. In the current era of technology, which requires all small industry players to improve their abilities in the field of communication and information technology, currently internet-based technology creates a business environment that is no longer concerned with time and distance. The implementation of sales education through social media is a service to the community with the aim of helping the Sabilulungan Women's Farmers' Demplot Group to increase sales and income so that the Demplot Farmers' Group can survive in today's business competition. The activity method in community service uses a technique of delivering material verbally to the participants, this community service has a background problem because agricultural products from the Demonstration Farmer Group still sell conventional products and have not made good use of online sales using social media and e-commerce platforms. The results of the research carried out were able to innovate marketing which was originally conventional into marketing that utilizes technological developments, namely by conducting electronic marketing by utilizing social media and E-commerce platforms as sales media.